Kreativitas Pembelajaran PAI untuk Meningkatkan Proses Belajar Siswa SMAN 12 Surabaya - Moh. Solehuddin (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2019)
Teachers in carrying out their duties are expected to change the new paradigm. One of these paradigms is that teachers must have creativity in the learning process. Learning creativity is the ability to create or create new things or new combinations based on existing data, information and elements, have high-level thinking skills, and produce creative works obtained through knowledge / life experience and are able to come up with creative ideas. innovative in learning. Given the importance of creativity in learning, in schools it is necessary to develop a learning strategy that can develop creativity. These strategies include the selection of approaches, methods or models, tactics or learning techniques. Islamic religious education is fundamental in the formation of student characteristics. Creativity in various learning models, PAI teachers are expected to master it. A quality learning process will generate student interest and achievement.